Pengaruh Gaya Kepemimpinan Kepala Sekolah terhadap Motivasi Guru di SMK DR SOETOMO Surabaya - Rozy Hardiyan Pratama; Iswati Iswati (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to examine the influence of the principal leadership style on teacher motivation at DR SOETOMO Vocation School, Surabaya. This research is motivated by the importance of the leadership role of school pricipals in creating a conducive work environment and motivating teaching staff to achieve optimal performance. This research uses a quantitative approach with a survey design, involving 31 teachers as respondent. Data was collected through a questionnaire designed to measure the leadership style and level of teacher motivation. Data analysis was carried out using simple linear regression techniques to identify the relationship between leadership style variables and motivation. The research results show that leadership has a positive and significant influence on teacher motivation. Transformational and participative leadership styles tend to increase teachers motivation, while authoritarian leadership styles have a less significant effect. These findings suggest the need for principals to adopt a more supportive and empowering leadership style to increase teacher motivation and performance. This research contributes to the development of effective leadership strategis in educational environments.